EFFECTIVENESS OF ROSELLA AS AN ANTI-INFLAMMATORY - Uno, Salsabila Putri; Winaprilia, Salsabila Sri; Putri, Sekar Riandani; Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2024)
Rosella flower (Hibiscus sabdariffa L.) can be used in the health sector. Rosella petal extract contains flavonoids such as gossypetin, hibiscetin, sabdaretine, alkaloids, and saponins. Rosella has properties such as an antiseptic, diuretic, anti-inflammatory, antibacterial, antioxidant, and can increase endurance. This paper discusses the anti-inflammatory effect of the rosella plant. The purpose of this article is to describe the effectiveness of rosella plant as an anti-inflammatory. This article collects research results from journals, textbooks, and websites accessed through the National Library of Medicine and Google scholar databases as a method. The reference source inclusion criteria are published in 2012-2022 with topics that are in line with the effectiveness of rosella as an anti-inflammatory. The reference source exclusion criteria were literature published before 2012. A total of 25 references were found, 15 references were selected, and 10 references were excluded. The studies have shown that the content of rosella flower extract is able to inhibit the cyclooxygenase enzyme thereby inhibiting the synthesis of inflammatory mediators, namely leukotrienes and prostaglandins and reducing the number of neutrophils so that it can accelerate the wound healing process, however administration of high doses of rosella extract is less effective as an anti-inflammatory because the levels of flavonoids decreased activity at high extract concentrations.